BELAJAR MENGHARGAI KEARIFAN LOKAL DARI YESUS DALAM MATIUS 22:32 - Noel Ghota Prima Bayu Surbakti (SEKOLAH TINGGI TEOLOGI STAR'S LUB LUWUK BANGGAI, 2019)
Churches in Indonesia live in ethnical and cultural diversity. We can find much local wisdom which lately continues to preserve. But not all churches want to receive local wisdom because there is an opinion that local culture is contrary to the Christian faith. Therefore in this paper, I want to invite the churches in Indonesia to open space for local wisdom. My effort is encouraging the churches to look at the figure of Jesus, who popularized the local wisdom called the tradition of Theos Patros. Theos Patros tradition is the oldest tradition of the nation of Israel and has been known since the ancestors' era but is no longer popular in the time of Jesus. But Jesus re-popularized the tradition because that tradition has a high noble value in line with the emphasis of the Gospel of Matthew.